1976
DOI: 10.1017/s0022143000030756
|View full text |Cite
|
Sign up to set email alerts
|

The freeezing behaviour of supercooled water drops

Abstract: An electrodynamic containment system has been used to study the freeezing behaviour of supercooled water drops, of radius range 25 to 90 μm. The drops were freozen at temperatures between 0 and — 29°C in an environment whose relative humidity was approximately 90% with respect to ice. Freezing events were observed visually and photographically, and measurements were mager of the accompanying freactional mass loss Δm/m. The most common moger of freeezing (70% of the drops studied) resulted in an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These authors recognized that the charged droplets existing in thunderclouds could undergo evaporation and Coulomb fission events, possibly producing bare ions of chemicals and salts dissolved in the droplets. Coulomb fission (Rayleigh bursting) was previously reported for supercooled water droplets evaporated to the Rayleigh limit . Calculations by Thompson and Iribarne, based on data available at the time, concluded that the salts and particulate matter in a cloudwater drop would mostly prevent the release of bare ions, but formation of the highly charged smaller droplets by coulomb fission might still occur and be involved in lightning initiation .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These authors recognized that the charged droplets existing in thunderclouds could undergo evaporation and Coulomb fission events, possibly producing bare ions of chemicals and salts dissolved in the droplets. Coulomb fission (Rayleigh bursting) was previously reported for supercooled water droplets evaporated to the Rayleigh limit . Calculations by Thompson and Iribarne, based on data available at the time, concluded that the salts and particulate matter in a cloudwater drop would mostly prevent the release of bare ions, but formation of the highly charged smaller droplets by coulomb fission might still occur and be involved in lightning initiation .…”
Section: Resultsmentioning
confidence: 94%
“…In triboluminescence, which is sometimes called fractoluminescence, crystal cracking is believed to cause charge separation at the separated surfaces. , The gas-phase charged particles splintered from the matrix surface then release bare analyte ions upon matrix sublimation. The experiments with 3-NBN, along with the fact that ice is implicated in charge generation in thunderclouds and is known to undergo triboluminescence convinced us to determine if freezing solvent is a means of ion formation for use in MS. Charged ice particles have been produced by collisions in the laboratory and observed visually, as well as photographed spontaneously leaving the surface of freezing water droplets; apparently a result of a splintering process. , …”
mentioning
confidence: 99%
“…At 25°C, we speculate that the cooling effect of the gas expansion through the capillary inlet freezes the droplet, which subsequently shatters in a way that leads to ion formation. Ion emission from ice is known to be possible 21,22 . Droplet freezing and shattering has been speculated as a source of ion formation,23,24 and a previous SAI study utilized a cold capillary inlet to freeze droplets containing analyte flowing into the capillary to enhance ion formation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Water content, droplet size, surface type and ambient conditions have been identified as having an influence on the process of ice formation in jet fuel [48]. One of the most important factors impacting the ice formation in jet fuel is the presence of supercooled water droplets [127]. According to Schmitz et al, ice formation is a result of fine water droplets that have precipitated out and solidified into ice crystals [10].…”
Section: Ice and Its Behaviour In Jet Fuelmentioning
confidence: 99%